Social preferences: Fundamental characteristics and economic consequences - Ernst Fehr; Gary Charness (University of Zurich, Department of Economics, 2023)
We review the vast literature on social preferences by assessing what is known about their fundamental properties, their distribution in the broader population, and their consequences for important economic and political behaviors. We provide, in particular, an overview of the empirically identified characteristics of distributional preferences and how they are affected by merit, luck, and risk considerations as well as by concerns for equality of opportunity. In addition, we identify what is known about belief-dependent social preferences such as reciprocity and guilt aversion. The evidence indicates that the big majority of individuals have some sort of social preference while purely selfinterested subjects are a minority. Our review also shows how the findings from laboratory experiments involving social preferences provide a deeper understanding of important field phenomena such as the consequences of wage inequality on work morale, employees' resistance to wage cuts, individuals' self-selection into occupations and sectors that are more or less prone to morally problematic behaviors, as well as issues of distributive politics. However, although a lot has been learned in recent decades about social preferences, there are still many important, unresolved, yet exciting, questions waiting to be tackled.
Keywords: 330; Soziale Wohlfahrtsfunktion; Theorie; Wirkungsanalyse